Zn-doping for reduced hysteresis and improved performance of methylammonium lead iodide perovskite hybrid solar cells. (September 2017) - Zhao, Wangen; Yang, Dong; Yang, Zhou; Liu, Shengzhong (Frank)
Abstract: The high efficiency and low-toxicity are the two main objectives for all perovskite solar cells (PSCs) towards large scale commercialization. Herein, ecology-benign Zn was introduced to partially replace the noxious Pb in the typical Pb-based perovskite absorber layer owing to its low-toxicity, high-richness in the crust, suitable valence states, and good stability against oxidation and reduction. It is found that the addition of Zn with a certain amounts significantly improves the crystalline quality, enlarges the grain sizes in the perovskite thin films, reduces the non-radiative recombination loss and lengthens the carrier lifetime, leading to the improved photovoltaic performance and eliminated hysteresis. It is demonstrated that Zn doping is an effective strategy to replace Pb to achieve superior solar cell performance with reduced Pb usage. Graphical abstract: Highlights: The divalent Zn cation with low-toxicity, high-richness, good stability is successfully introduced to the perovskite films. The addition of Zn effectively suppressed the notorious hysteresis, making the PCE value more reliable. The approach provides a possibility to achieve the less-Pb perovskite layer by optimizing the fabrication process of films.